PILIH PETANI VIETNAM ATAU PETANI INDONESIA?: PROTEKSI DAGANG PERTANIAN DALAM PERSPEKTIF EKONOMI POLITIK - Wahyu Riawanti (Universitas Ahmad Dahlan, 2013)
This study emphasizes about Indonesian agricultural protection in international trade. This issue became prominent after the surge of imported products especially a decade after Indonesia followed what is instructed by IMF to liberalize international trade in most of commodities. The argument of tis studi is whether government execute the policy of agricultural protection in political economy perspective, considering that government not only needs to follow international tradeade regulation, but also require to protect any infant indistry with lack of technolog such as agriculture sector. This article focused in three main things: (1) protection of agricultural commodity is indeed difficult (2) the policy seemed make it it more complicated, (3) policy is about whose interest counts. Rice commodity is used to simplify the explanation with a brief comparation with other few commodities.